2006
DOI: 10.1017/s0265021505001912
|View full text |Cite
|
Sign up to set email alerts
|

The impact of intraoperative propofol administration in the prevention of postoperative pruritus induced by epidural morphine

Abstract: Propofol-based general anaesthesia compared to thiopental-sevoflurane-based anaesthesia reduces the incidence and severity of pruritus induced by a single injection of 3 mg epidural morphine with ropivacaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In man, propofol has been reported to be an effective treatment for pruritus associated with epidural or intrathecal opioids (Horta et al 2006;Kostopanagiotou et al 2006). However, a meta-analysis by Kjellberg and Tramèr (2001) of 22 trials in 1477 patients reported no evidence of antipruritic efficacy of prophylactic propofol.…”
Section: Discussionmentioning
confidence: 99%
“…In man, propofol has been reported to be an effective treatment for pruritus associated with epidural or intrathecal opioids (Horta et al 2006;Kostopanagiotou et al 2006). However, a meta-analysis by Kjellberg and Tramèr (2001) of 22 trials in 1477 patients reported no evidence of antipruritic efficacy of prophylactic propofol.…”
Section: Discussionmentioning
confidence: 99%
“…This observation could be partially attributed to the antioxidative capability of mannitol. [46][47][48] Typical phase and uorescence images showing the formation of a single cell aggregate of uniform size in each ACA microcapsule with high cell viability aer 7 day culture of the Journal of Materials Chemistry B Paper encapsulated ES cells in complete ES cell medium are given in Fig. 2C and D, respectively.…”
Section: Capability Of the Aca Microcapsule For Encapsulating And Cul...mentioning
confidence: 99%
“…It exerts its antipruritic action through the inhibition of the posterior horn transmission in the spinal cord. [1148495051525354] Many studies have been carried out with the sub-hypnotic propofol doses ranging from 10 mg bolus to 30 mg over 24 h, but results were conflicting. [51125]…”
Section: Introductionmentioning
confidence: 99%